Screening Method for the Identification of Compounds That Activate Pregnane X Receptor. Issue 12 (5th December 2022) - Lynch, Caitlin; Sakamuru, Srilatha; Xia, Menghang
Abstract: The pregnane X receptor (PXR) is a nuclear receptor found mainly in the liver and intestine, whose main function is to regulate the expression of drug‐metabolizing enzymes and transporters. Recently, it has been noted that PXR plays critical roles in energy homeostasis, immune response, and cancer. Therefore, identifying chemicals or compounds that can modulate PXR is of great interest, as these can result in downstream toxicity or, alternatively, may have therapeutic potential. Testing one compound at a time for PXR activity would be inefficient and take thousands of hours for large compound libraries. Here, we describe a high‐throughput screening method that encompasses plating and treating HepG2‐CYP3A4‐hPXR cells in a 1536‐well plate, as well as reading and interpreting assay (e.g., luciferase reporter gene activity) endpoints. These cells are stably transfected with a human PXR expression vector and CYP3A4 ‐promoter‐driven luciferase reporter vector, allowing the identification of compounds that activate PXR through cytochrome 450 3A4. We also describe how to analyze the data from each assay and explain follow‐up steps, namely pharmacological characterization and quantitative polymerase chain reaction (qPCR) assays, which can be performed to confirm results from the original screen. These methods can be used to identify and confirm hPXR activators after completion of a compound screening. Published 2022. This article is a U.S. Government work and is in the public domain in the USA. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Establishment of a high‐throughput assay to identify hPXR activators Basic Protocol 2 : Quantitative high‐throughput screening a compound library to classify hPXR activators Basic Protocol 3 : Performing pharmacological characterization and qPCR assays to confirm hPXR activators